2006
DOI: 10.1007/s10562-006-0130-y
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the catalytic performance of γ-alumina-supported Co(Ni)–Mo(W) HDS catalysts prepared by urea-matrix combustion synthesis

Abstract: A comparative study of the influence of Co (or Ni) promoter loadings and the effect of different sulfurizing agents and sulfurizing temperatures on the structure, morphology and catalytic performance of Mo-or W-based hydrodesulfurization (HDS) catalysts was carried out. Catalyst performance using a tubular fixed-bed reactor and the HDS of thiophene as a model reaction was evaluated. The oxidic and sulfurized states of the HDS catalysts were characterized by laser Raman spectroscopy, thermogravimetric analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The second mass reduction is attributed to the total decomposition of Ni and Mo precursor salts as well as decomposition of remained organic additives resulting in evolution of CO 2 , N 2 and H 2 O. [6,33]. The second mass loss which is related to combustion reaction in prepared nanocatalysts with citric acid, urea, glycine and ethylene glycol is 33%, 28%, 34% and 12%, respectively.…”
Section: Nanocatalyst Performance Testmentioning
confidence: 98%
See 1 more Smart Citation
“…The second mass reduction is attributed to the total decomposition of Ni and Mo precursor salts as well as decomposition of remained organic additives resulting in evolution of CO 2 , N 2 and H 2 O. [6,33]. The second mass loss which is related to combustion reaction in prepared nanocatalysts with citric acid, urea, glycine and ethylene glycol is 33%, 28%, 34% and 12%, respectively.…”
Section: Nanocatalyst Performance Testmentioning
confidence: 98%
“…The combustion technique is a fast, simple and energy saving method which is based on the redox reaction between an organic compound (fuel) and oxidizer agent, including sulfates, nitrates and carbonates [31,32]. A wide variety of organic compounds such as urea [33], glycine [34,35], citric acid [36], ethylene glycol [37], starch [38] and a mixture of them [39] have been used through combustion method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover it is suggested that the pronounced asymmetry results from the partial incorporation of carbon into the MoS 2 structure, at least in the surface, and from increased bending and folding of the MoS 2 layers [34,45]. Recently, Raman studies of promoted catalysts obtained by urea-matrix combustion synthesis on alumina support revealed similar distortions of MoS 2 [46]. In the mid-IR region a broad band centered at around 1100 cm )1 is observed (see figure 5).…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…Therefore, the amount of sulfur and nitrogen compounds in fuels should be decreased to provide a clean environment. Hydrodesulfurization (HDS) (Gao et al, 2011;González-Cortés et al, 2006;Hajjar et al, 2015Hajjar et al, , 2016aHajjar et al, , 2017aHajjar et al, , 2017bHuirache-Acuña et al, 2012;Mendoza-Nieto et al, 2015;Miller et al, 2000;Shan et al, 2015) and hydrodenitrogenation (HDN) (Sundaramurthy et al, 2006;Zepeda et al, 2016) are the main processes considered for reducing the Total Sulfur (T.S.) and Total Nitrogen (T.N.)…”
Section: Introductionmentioning
confidence: 99%